A High Efficiency Ultra Thin (1.8 um) CdS/CdTe p-i-n Solar Cell with CdTe and Si as BSF layer - Nahid A. Jahan; Md. Minhaz Ul Karim; M. Mofazzal Hossain (Advances in Science, Technology and Engineering Systems Journal, 2018)
CdTe-based photovoltaic (PV) cells provide the lowest EBPT (energy payback time) and emit less amount of GHG (green house gases) among different types of PV cells. Thus, it is very essential to enhance the efficiency of CdTe-based solar cells. A high efficiency CdTe/CdS p-i-n heterostructure solar cell is designed and the performance of the cell is investigated. All the simulations have been done using AMPS 1D (Analysis of Microelectronic and Photonic Structures) simulator. The cell consists of a transparent conducting oxide (TCO) layer (ZnO), a window layer (n-type CdS), an intrinsic layer (CdTe), an absorber layer (p-type CdTe) and a highly doped CdTe and Si as back surface field (BSF) layer. After the optimization of layer thicknesses and doping densities of different layers, we obtained a conversion efficiency of 26.01% for a total cell thickness of 1.8 um. It is also found that the conversion efficiency can be increased by simply increasing the thickness of intrinsic layer. At 1.5 AM solar irradiance, the proposed cell structure attained a Voc of 1.09 V, a Jsc of 26.78 mA/cm2, and a fill factor of 89%, reaching an overall conversion efficiency of 26.01% with CdTe as BSF layer.
Keywords: CdTe/CdS; BSF layer; Cell efficiency; Intrinsic layer